Mapeamento de recursos pesqueiros: Um enfoque etnoecológico - Cavalcante, Lamara Silva e (2019)
Artisanal fishing is an activity characterized by the small-scale exploitation of aquatic natural resources, which serves as a basis for family subsistence and as an economic source for fishing communities in different forms of organization. Local sensory research (CEL) of artisanal fishers in the communities of Barra de Mamanguape and Tramataia, located on the banks of the Mamanguape River estuary (ERM), north coast of Paraíba, northeastern Brazil. The aim of the study was to map and analyze ERM fishery resources through CEL in combination with the Geographic Information System (GIS). Eighty-eight artisanal fishers were engaged, 57 men and 31 women, using as qualitative techniques (semi-completed interviews, free listing and participatory mapping), and quantitative (Use Value, GIS, Cognitive Salience Index / ANTHROPAC 4.0). ). The results of the CEL survey on fishery resources were 19 distributions in 18 families. Cognitive Salience Index analysis indicated four disruptions for repetition and frequency of responses, the first of which contemplated one species, a second three species, a new six species disruption, and one last sort found in nine species. Regarding the use value (VU), the cultural knowledge domain of the species was defined by economic use and the most important species were Anomalocardia flexuosa (VU = 0.48) Mugil curema (VU = 0.36) and Ucides cordatus (VU = 23, 9). We used GIS to aggregate CEL into cognitive maps generated in ArcGIS 10.5-ESRI © -2017 software, which exhibited the characteristics of ERM fishing behavior. 49 fishing sites were mapped, the data indicating that 10 fishing sites are areas of major importance for ERM fishermen. The search for resources presented differences according to the species and the environment used. Fishermen's CEL on fishing sites demonstrates that, in addition to being biophysical resource areas, these sites represent important historical / cultural markers of local users. Therefore, information on local marine biotopes, which are highly productive and moderately impacted by human activities and fishermen's usual maritime tenure, is considered indispensable to assist resource management and management of marine protected areas, and to develop biogeographic data for comparison changes in the way fish stocks are exploited.